(untitled) (Indian Journal of Arid Horticulture, 2025)
In arid regions, there is a growing interest in the cultivation of medicinal crops, as discussed in various forums. However, indigenous woody species, which are well-adapted to harsh climatic conditions, have not received the necessary attention compared to introduced species. There is a need to enhance farmers’ livelihoods by increasing farm income through the integration of suitable woody and herbaceous medicinal plant species into existing farming systems. This paper reviews the woody perennials of medicinal importance and explores potential avenues for integrating them into different agroforestry land-use systems (ALUS) from a farming system perspective.